Contemporary research on the spatial relations between the public library and the city : Suvremena istraživanja prostornih odnosa javne knjižnice i grada - Banović Đorđević, Ivana (Array, 2020)
Public library has been taking active roles in the urban transformation strategies over the last twenty years. This paper researches origins and defines the public library and the city relation, systematizing those roles and strategies through literature review. The library and the city relation is confirmed as mutual and the public library is defined as the „place” in the city fabric in the accordance with its architectural attributes and location.